Translations, Transcreations and Transrepresentations of India in the Italian Media - Di Giovanni, Elena (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2008)
AbstractThis paper explores the dynamics of cultural representation through the media, making special reference to the translation of cultural traits that occur in the cinema and television. By taking into account several films and television commercials which were broadcast in Italy over a five-year span, featuring variously complex and stratified translations of India, an attempt is made to define and explore the different guises which translation can take when the object of transfer is not merely language and its purpose is not merely communication. The transformations which have been identified in the use and transfer of Indian cultural traits through the Italian media are here discussed in terms of translation, transcreation and transrepresentation.